Characterization of RF Voltage and Self-Bias under Power Variations in 13.56 MHz RF Sputtering System - Aprilia Dewi Ardiyanti; Aslam Chitami Priawan Siregar; Ni’matut Tamimah (Faraday: Journal of Fundamental Physics, Research, and Applied Science, 2025)
RF Sputtering has been widely used as a deposition system on thin films. This study examines the impact of input power on RF voltage and self-bias voltage in an RF Sputtering system operating at a frequency of 13.56 MHz. Power variations were carried out in the range of 50 to 150 Watts to observe the changes in voltage produced during the plasma formation process. The experimental results indicate a linear dependency between power and both voltages, with a coefficient of determination (R²) above 0.9 and slope values of 2.86 and 0.96 for the RF voltage and self-bias voltage, respectively. The observed linear correlation indicates that adjusting power regulation can be utilized as an effective control parameter for both voltages, enabling the production of uniform and high-quality thin film deposition.